TEACHING INDONESIA LANGUAGE FOR KUN SHAN UNIVERSITY STUDENTS AND VOLUNTEERING FOR CAMPUS GUESTS FROM INDONESIAN UNIVERSITIES TAINAN – TAIWAN R. O. C. - Mustakim Mustakim; Tsai Mei_Tuan; Elihami Elihami; Musdalifah Musdalifah (LP2M Universitas Muhammadiyah Enrekang, 2020)
Community service regarding the teaching Indonesia language and volunteering were initiated by the Chinese Language Center of Kun Shan University, Tainan - Taiwan R.O.C. This activity was one of the programs implemented by CLC - KSU in collaboration with international students include me from STKIP Muhammadiyah Enrekang. The purpose were to teach Indonesia language to all Kun Shan University students who were eager to learn Indonesian and to help Indonesia partners from different universities in Indonesia who came to visit Kun Shan University. I did this activity in the campus environment. When teaching Indonesia language, I prefer to teach in canteens or campus cafes to make it more fun while volunteering activities of course I became a translator of Mandarin into Indonesian or vice versa. When Indonesian guests came to KSU, the campus and I took them around and introduced the campus. While my partner in Indonesia prepared the materials and the lesson plans and also the KSU students sometimes did a video call to have long distance conversation.